IMPLEMENTASI SISTEM POINT DALAM MENINGKATKAN KETERTIBAN SISWA DALAM MENTAATI ATURAN SEKOLAH PADA SISWA KELAS IX SMP NEGERI 3 CIGEMBLONG TAHUN PELAJARAN 2018/2019 - Achmad Wawan (Jurnal Penelitian Bimbingan dan Konseling, 2019)
abstract One way to increase student order in adhering to school rules is by implementing a point system, so because at Cigemblong 3 Public Elementary School, the problem of order is very prominent, so BK teachers want to apply the point system to students. The main purpose of this study is to provide lessons for students about the importance of discipline in adhering to school rules. The techniques and tools for collecting data in this study are interviews, observations and document analysis. While the data analysis uses quantitative analysis mixed with qualitative analysis. The results of the observation of the first cycle resulted in a score of 11 which showed that the order of students in obeying the rules of the school had increased enough. Then continued the second cycle which resulted in a score exceeding the first cycle which is 13 which shows that the order of students in obeying the rules of the school has greatly increased. The final result of this study is that the method of giving points can improve student order, adhere to school rules. Keywords: Method of Giving Points, Improving Student Order, Obeying School Rules.